Role of Potassium Ions Quantum Tunneling in the Pathophysiology of Phantom Limb Pain - Alrabayah, Mustafa (Brain Sci, 2020)
(1) Background: multiple theories were proposed to explain the phenomenon of phantom limb pain (PLP). Nevertheless, the phenomenon is still shrouded in mystery. The aim of this study is to explore the phenomenon from a new perspective, where quantum tunneling of ions, a promising field in medical practice, might play a major role. (2) Methods: investigators designed a quantum mathematical model based on the Schrödinger equation to examine the probability of potassium ions quantum tunneling through closed membrane potassium channels to the inside of phantom axons, leading to the generation of action potential. (3) Results: the model suggests that the probability of action potential induction at a certain region of the membrane of phantom neurons, when a neuron of the stump area is stimulated over 1 mm(2) surface area of the membrane available for tunneling is 1.04 × 10(−2). Furthermore, upon considering two probabilities of potassium channelopathies, one that decreased the energy of the barrier by 25% and another one by 50%, the tunneling probability became 1.22 × 10(−8) and 3.86 × 10(−4), respectively. (4) Conclusion: quantum models of potassium ions can provide a reliable theoretical hypothesis to unveil part of the ambiguity behind PLP.